Editorial PPP 16(2) - Psicossociologia desde a América Latina - Takeiti, Beatriz Akemi; Costa, Samira Lima da; Pardo, Catalina Revollo; Guerra, Claudia Tovar; Miranda, Claudia (Revista Pesquisas e Práticas Psicossociais, 2021)
Psicossociologia desde a América Latina